THE CHANGING LANDSCAPE OF INTERNATIONAL HIGHER EDUCATION - Zhakypova, Fatima (My University, 2013)
“The development of international higher education in leading countries of the world is undergoing an influence of global tendencies. One of them is the massification of higher education”--
Keywords: Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education::International education; international education; education reforms; higher education